APLIKASI SISTEM PAKAR UNTUK MENDETEKSI KERUSAKAN TELEPON SELULAR BERBASIS WEB - Wahyu Widarti, Dinny; Setyowati, Endah (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
An expert system is a computerized application programs that seek to imitate the reasoning process of an expert in solving problems or mimic the reasoning of an expert in solving the problem specification or can be said to be a duplicate of an expert by knowledge stored in the knowledge base and in the process to solve problems. The use of mobile phone has almost become a necessity in todays era. Inside his use of a mobile phone are also vulnerable to damage, often directly determine the damage to their mobile phone without knowing what the main cause of the malfunction. It is therefore considered very necessary to have applications that can provide information like an expert. Keywords: Expert Systems Application, Mobile PhoneÂ